Death: A Graveside Companion - Joanna Ebenstein
Death is an inevitable fact of life. Throughout the centuries, humanity has sought to understand this sobering thought through art and ritual. The theme of memento mori informs medieval Danse Macabre, the Tibetan Book of the Dead, Renaissance paintings of dissected corpses and (3z(Banatomical Eves,(3y (BGothic literature, funeral effigies, Halloween, and paintings of the Last Judgment. Deceased ancestors are celebrated in the Mexican Day of the Dead, while the ancient Egyptians mummified their dead to secure their afterlife.s